Synthesis and selected transformations of 2-unsubstituted 1-(adamantyloxy)imidazole 3-oxides: straightforward access to non-symmetric 1,3-dialkoxyimidazolium salts - Mlostoń, Grzegorz; Celeda, Małgorzata; Urbaniak, Katarzyna; Jasiński, Marcin; Bakhonsky, Vladyslav; Schreiner, Peter R.; Heimgartner, Heinz (Beilstein Journal of Organic Chemistry, 2019)
Adamantyloxyamine reacts with formaldehyde to give N-(adamantyloxy)formaldimine as a room-temperature-stable compound that exists in solution in monomeric form. This product was used for reactions with α-hydroxyiminoketones leading to a new class of 2-unsubstituted imidazole 3-oxides bearing the adamantyloxy substituent at N(1). Their reactions with 2,2,4,4-tetramethylcyclobutane-1,3-dithione or with acetic acid anhydride occurred analogously to those of 1-alkylimidazole 3-oxides to give imidazol-2-thiones and imidazol-2-ones, respectively. Treatment of 1-(adamantyloxy)imidazole 3-oxides with Raney-Ni afforded the corresponding imidazole derivatives without cleavage of the N(1)–O bond. Finally, the O-alkylation reactions of the new imidazole N-oxides with 1-bromopentane or 1-bromododecane open access to diversely substituted, non-symmetric 1,3-dialkoxyimidazolium salts. Adamantyloxyamine reacts with glyoxal and formaldehyde in the presence of hydrobromic acid yielding symmetric 1,3-di(adamantyloxy)-1H-imidazolium bromide in good yield. Deprotonation of the latter with triethylamine in the presence of elemental sulfur allows the in situ generation of the corresponding imidazol-2-ylidene, which traps elemental sulfur yielding a 1,3-dihydro-2H-imidazole-2-thione as the final product.
Keywords: alkoxyamines; imidazole N-oxides; imidazolium salts; nucleophilic carbenes; sulfur transfer reaction